ANALISIS KEAMANAN JARINGAN VIRTUAL PRIVATE NETWORK (VPN) PADA SISTEM ONLINE MICROBANKING (Kasus di BMT Al Ikhlas Yogyakarta) - , Marti Widya Sari; , Widyawan, S.T., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Virtual Private Network (VPN), is a network created to conduct transactions encrypted data between two or more authorized network users. VPN network using the Internet so that all the safety factor becomes very important. Some of the attacks that may occur in the Internet network is a Denial of Service (DoS) attacks, sniffing, spoofing, session hijacking, and many more. Research on the analysis of network security Virtual Private Network (VPN) is done in BMT Al Ikhlas Yogyakarta, which has a headquarters and several branch offices and use VPN to conduct online transactions between branches. VPN software used is based, namely Hamachi version 1.0.3.0 type of free license. In addition, also use PPTP (Point to Point Tunneling Protocol) VPN Mikrotik as a backup if the Hamachi VPN connection to crash. Research carried out by using the method of sniffing (eavesdropping) on every packet that passes through the network, then view and analyze the results. The instrument used was the Wireshark Network Protocol Analyzer. The study was conducted on the network without a VPN, hamachi VPN using IPSec technology (IPSecure) and Mikrotik VPN using PPTP technology. The results showed that without a VPN network more vulnerable to security attacks on the network, while for the more secure VPN network. This can be seen from the results of testing the system using Wireshark on a network without a VPN configurations and VPN networks. The results for the different VPN technologies, namely IPSec and PPTP is also different. The constraints experienced during the study is the absence of SOP (Standard Operating Procedure) for a network system that is currently used, the documentation for network monitoring and allocation of time for research in light of the crowded office operating hours. The recommendations can be given, among others, is the use Mikrotik routers for more maximized, replacement of some network equipment for network performance to be better and the making of documentation for network monitoring that is done routinely.